CHANGE MANAGEMENT IN FOUNDATION ISLAMIC RELIGIOUS HIGH SCHOOLS KALIANDA DEVELOPMENT, SOUTH LAMPUNG - Junaidah, Junaidah; Anggraini, Dinda Tri; Irwandi, Feri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Educational organizations will experience changes. This also happens in educational institutions such as STAI YASBA. Change management at STAI YASBA cannot be separated from leaders who have a visionary leadership style whose management has a spirit of implementing change. Organization members have a high commitment to implementing change and are able to maintain and develop change. However, this does not mean that the change management carried out does not have obstacles, but there are quite a few problems that hinder the change from taking place. This is what attracted the author's attention to further research regarding change management at STAI YASBA. This research aims to: 1) find and describe the identification of changes; 2) find and describe change planning; 3) find and describe the implementation of changes; 4) find and describe the evaluation of changes. This type of research is qualitative with a descriptive approach based on case studies. Data collection techniques use observation, interviews and documentation. Data analysis uses Miles and Huberman's theory through three stages, namely data reduction, data presentation and drawing conclusions or data verification. The research results show that there are four stages of change management implemented by STAI YASBA, the stages carried out are; 1) identify changes by means of leaders observing members' performance results and holding regular meeting activities; 2) planning change by determining the means and capabilities to change social change, social order and organize social change; 3) implementation of change with three phases, namely unfreezing, action (change) and determination (refreezing); 4) evaluate changes by holding meetings to gather opinions and discuss the implementation of changes to provide alternative solutions.